ENHANCING THERAPEUTIC STRATEGIES FOR HERPETIC STOMATITIS: A COMPREHENSIVE APPROACH TOWARDS IMPROVED PATIENT OUTCOMES - Rashidbek Tuychiyev (Western European Studies, 2024)
This research investigates an enhanced approach to treating herpetic stomatitis, a significant oral health concern caused by the herpes simplex virus (HSV). The study involves 25 participants, divided into two groups. The main group receives an improved complex treatment, including Proposol Spray and lyzobact tablets alongside conventional therapy, while the comparison group follows traditional treatment methods. Clinical, immunological, and statistical research methods were employed to assess treatment outcomes. Results demonstrate the superior efficacy of the enhanced complex treatment, emphasizing the importance of individualized dosages and continual evaluation of pharmacodynamic properties. Incorporating Proposol Spray and lyzobact shows promising therapeutic effects, offering valuable insights for advancing herpetic stomatitis treatment
Keywords: Herpetic stomatitis; Herpes simplex virus; Complex treatment